Clinical and epidemiological characteristic of chronic hepatitis C in the republic of Tyva - A. A. Saryglar; S. O. Dongak; A. D. Ibrohimova; K. E. Novak; E. V. Esaulenko (Журнал инфектологии)
Aim: To assess the current epidemiological situation and establish the dominant clinical profile of patients with chronic hepatitis C, taking into account the stage of the disease and the molecular genetic characteristics of the virus in the Republic of Tyva.  Materials and methods: Based on the annual reports of the dispensary observation office of the Infectious Hospital of the Republic of Tyva, an electronic database was developed using the licensed Office Excel 2016 program, which included results on the health status of patients, clinical, laboratory and instrumental data, including molecular biological data with the determination of HCV genotypes. The analysis of the data of the state statistical reporting of infectious morbidity in the Russian Federation (form №2 “Information on infectious and parasitic diseases”) was carried out. Analytical tables developed by specialists of the Scientific and Methodological Center of the Saint-Petersburg Pasteur Institute for the period 2012-2022. The data of the Reference Center for Monitoring Viral Hepatitis of the Federal State Budgetary Institution “Central Research Institute of Epidemiology” of Rospotrebnadzor were used.  Results. Over the past two years, the decrease in incidence in the Republic of Tyva is likely due to a decrease in the number of examinations, a decrease in patients seeking outpatient care, and insufficient screening in the context of the COVID-19 pandemic. Clinical, laboratory and instrumental examination of patients with HCV revealed the predominance of HCV-infected genotype 1 (49.4%), with F0-F2 fibrosis in 79% of cases. The clinical profile of typical patients with chronic hepatitis C was established; whose share in the total structure of the examined was 38.4%.  Conclusion: There is a tendency to reduce the incidence of chronic hepatitis C in the Republic of Tyva. Based on the clinical information base, the most typical characteristics of chronic hepatitis C patients living in the Republic of Tyva have been established.